Reflecting and learning from the mode of multifunctional food markets in Macau - Gu, Yang (2023)
Being one of the oldest public functions in human history, markets always play important roles in urban space. Being the centre of trading, markets indicated the scale of cities. As cities emerged, markets were the economic centres of the city, as important as churches. But things are changing now, markets are in danger. The number of markets is declining, and many are struggling to survive facing the changes in the economic system.